Zwitterionic compounds are less ecotoxic than their analogous ionic liquids - Jesus, Fátima (2022)
Zwitterionic compounds (ZIs) have been attracting much attention due to their properties. Unlike ionic liquids – constituted by separated ions – the ZI structures with their cations and anions covalently bonded exhibit added complexity and diversity, suggesting that their ecotoxicological behavior should probably not be extrapolated from those of ionic liquids. This study addresses the aquatic toxicity of ZIs towards the bacterium Allivibrio fischeri and the microalga Raphidocelis subcapitata. Sixteen ZIs comprising five different cationic groups (ammonium, imidazolium, pyridinium, pyrrolidinium and piperidinium) and two anionic groups (sulfonate and carboxylate) were studied, and the relationships between their structure and toxicity are reported. All studied ZIs are harmless or practically harmless for both microalga and bacterium (median effective concentration, EC50 >100 mg L−1), presenting a significantly lower hazardous potential to aquatic species than their ionic liquid counterparts. The results also show that the increased hydrophobicity of ZIs, owing to the increase of the cation alkyl chain or the spacer length, has a significant influence on EC50 values for microalga, which in turn causes higher toxicity. However, no significant differences were observed when considering the various cationic groups of the ZIs studied, unlike what is known for ecotoxicity of the ionic liquids. Also, no relationships were found between the chemical structure of ZIs and EC50 values determined for the bacterium A. fischeri. The structural differences between ZIs and ionic liquids result in different mechanisms of interactions with microalgae and bacteria membranes, which may explain why the ecotoxicity heuristic rules previously reported for ionic liquids do not seem to apply to ZIs.